Atomistic mechanism of leptin and leptin-receptor association. Issue 6 (13th April 2023) - López-Hidalgo, Marisol; Caro-Gómez, Luis A.; Romo-Rodríguez, Rubí; Herrera-Zuñiga, Leonardo D.; Anaya-Reyes, Maricruz; Rosas-Trigueros, Jorge L.; Benítez-Cardoza, Claudia G.
Abstract: The leptin-leptin receptor complex is at the very core of energy homeostasis and immune system regulation, among many other functions. In this work, we built homology models of leptin and the leptin binding domain (LBD) of the receptor from humans and mice. Docking analyses were used to obtain the coordinates of the native leptin-LBD complexes and a mixed heterodimer formed by human leptin and mouse LBD. Molecular dynamics (MD) simulations were performed using all models (monomers and heterodimers) as initial coordinates and the GROMACS program. The overall structural and dynamical behaviors are similar for the three complexes. Upon MD simulations, several new interactions appear. In particular, hydrophobic interactions, with more than 90% persistence, seem to be the most relevant for the stability of the dimers, as well as the pair formed by Asp85Lep and Arg468LBD . This in silico analysis provides structural and dynamical information, at the atomistic level, about the mechanism of leptin-LBD complex formation and leptin receptor activation. This knowledge might be used in the rational drug design of therapeutics to modulate leptin signaling. Communicated by Ramaswamy H. Sarma